The Effect of Vitamin E Supplement in the Diet on Gonad Maturation of Nilem (Osteochilus hasselti, CV) - Nurbety Tarigan; Iman Supriatna; M. Agus Setiadi; Ridwan Affandi (Jurnal Perikanan Universitas Gadjah Mada, 2017)
The aim of this study was to examine the effect of vitamin E on gonad maturation and determining the best doses in improving gonad maturation in nilem fish. In this study used a flockof fishbrood which is never experienced spawning. There are 4 doses of vitamin E which used in this research following by 0, 125, 250, and 375 mg/kg. The results showed that fortifiedof vitamin E which were in feed significantly affected to the percentage of gonad development, gonadosomatic index (GSI), hepatosomatic index (IHS), fecundity, the diameter of eggs, and the percentage of egg maturity at P<0.05. The result showed that the best dose of vitamin E to reach gonad maturity was 375 mg kg-1 with six weeks maintenance. The percentage of gonad maturity was 100%, IGS was 11.50%, IHS was 0.34%, fecundity was 23.484 eggs/individual, the diameters of the eggs were 0.31 mm, and the percentage of mature eggs was 64.44%. These results supported the potential of feed additives such as vitamin E plays a critical role in enhancing gonad maturation in nilem fish thereby providing methods to improve fish reproduction